WLAN Mesh security association scheme in trusted computing environment - Yue-lei XIAO; Yu-min WANG; Liao-jun PANG; Shi-chong TAN (Tongxin xuebao)
To solve the existing problems caused by that the third version of WLAN authentication infrastructure (WAI) protocol was used to establish WLAN Mesh security association, a WLAN Mesh security association scheme based on an improved WAI protocol was proposed. The results of performance analysis of the scheme show that the scheme improves the performance of WLAN Mesh security association, especially decreases the overhead of the authentication server (AS). Then, on basis of this scheme, a WLAN Mesh security association scheme in trusted computing environment was put forward to meet the demand of trusted computing environment. Moreover, the two WLAN Mesh security association schemes were proved secure in the strand space model (SSM).